2022
DOI: 10.1111/anae.15742
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the outcome metric ‘days alive and at home’ in older patients after hip fracture surgery

Abstract: Days alive and at home´is a validated measure that estimates the time spent at home, defined as the place of residence before admission to hospital. We evaluated this metric in older adults after hip fracture surgery and assessed two follow-up durations, 30 and 90 days. Patients aged ≥ 70 years who underwent hip fracture surgery were identified retrospectively via hospital admission and government mortality records. Patients who successfully returned home and were still alive within 90 days of surgery were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…22 Days at home, specifically DAAH, in hip fracture patients has been assessed as a patient-centered outcome available from routine health data with strong face, construct, and predictive validity. [22][23][24] DAAH is a composite measure of days spent alive and not in a hospital, rehabilitation facility, emergency department, or nursing home after the index hospital admission. 22 DAAH is associated with physical function, quality of life, and supports (social and structural) that enable a person to stay at home-suggesting it is a useful and unique outcome to evaluate disparities in post-fracture recovery.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Days at home, specifically DAAH, in hip fracture patients has been assessed as a patient-centered outcome available from routine health data with strong face, construct, and predictive validity. [22][23][24] DAAH is a composite measure of days spent alive and not in a hospital, rehabilitation facility, emergency department, or nursing home after the index hospital admission. 22 DAAH is associated with physical function, quality of life, and supports (social and structural) that enable a person to stay at home-suggesting it is a useful and unique outcome to evaluate disparities in post-fracture recovery.…”
Section: Key Pointsmentioning
confidence: 99%
“…Work from Australia on days at home in hip fracture patients has revealed that 47% of patients did not return home by 30 days and 35% were not home at 90 days. 22 This work…”
Section: Introductionmentioning
confidence: 97%
“…For some, this may be the ability to return to independent living, for others a return to work, and indeed for some it will just be `staying alive´. There has been a move towards more patient-centred outcomes with measures such as days alive and out of hospital [9]. This may give the patient an idea of the healthcare burden they may have to endure after an operation, but ultimately still isn't what the patient really wishes to know.…”
Section: What About Death?mentioning
confidence: 99%
“…It could also look for differences between groups with different exposures as a formal case control or cohort study. It would be possible to go even further and use an outcome metric that would be important to patients, such as days alive and at home at 90 postoperative days [3].…”
Section: Data Collection and Synthesismentioning
confidence: 99%